PENGARUH TREND DAN DIGITAL MARKETING YOUTUBE TERHADAP BRAND AWARENESS INDONESIA TECH TREND PADA MAHASISWA UNIVERSITAS CIPUTRA SURABAYA ANGKATAN 2017 - Ongkowidjojo, Hogiharto; Pranoto, Henry (Universitas Ciputra Surabaya, 2023)
Indonesia Tech Trend is a company that runs in distribution field of technological products and other trendy products. Indonesia Tech Trend has been established since 2017. The products of Indonesia Tech Trend are technology products such as computers, computer equipment, and trendy electronic products. Indonesia Tech Trend exists to ensure people’s need, especially technological lovers, brand awareness can be influenced by some factors. In brand equity theory, there are some factors that affect brand awareness, that is, promotions belong to digital marketing and trend. The purpose of this research is to find out the effect of trends on brand awareness and the effect of digital marketing on Youtube on brand awareness. The method in this research is descriptive quantitative, with multiple linear regression analysis method using Statistical Product and Service Solution (SPSS). This research has the total sample of 110 respondents who are 2017 universitas ciputra students, Surabaya with the result of the research shows that trend does not effect on brand awareness and digital marketing Youtube effects and significant on brand awareness.